Sources and approaches across disciplines in Near Eastern studies - Union europeénne des arabisants et islamisants. (Leuven)
xiv, 562 s.
Keywords: "This volume collects papers from the 24th Congress of the Union Européenne des Arabisants et Islamisants (UEAI) in 2008 at the University of Leipzig. Original research and new approaches illustrate its theme of "Sources and Approaches across Disciplines in Near Eastern Studies". The studies span Muslim culture, civilizations, and intellectual thought in the medieval and modern periods. The contributions demonstrate the benefits of following methodological and interdisciplinary approaches that draw upon literary criticism, sociology and anthropology in the field of Qur'anic studies, religion, philosophy and mysticism; state and society; literature and rhetoric; philology and linguistics; mathematics and astronomy; art and epigraphy; and Islamic sciences and economic history. The volume also highlights the commonalities and overlaps that exist between these different branches and fosters cooperative study across a wide cultural, historical, and sociological milieu. Rather than following an isolated approach to their areas of study, academics in different fields of Islamic and Middle Eastern Studies benefited from one another’s methodologies, and collectively built a wide body of knowledge." --